1996
DOI: 10.1161/01.str.27.12.2304
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Brain Capillary Endothelial Thrombomodulin mRNA Expression

Abstract: These findings indicate astrocyte regulation of thrombomodulin mRNA expression in vitro and suggest an important role for the blood-brain barrier in the regulation of thrombomodulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…[31][32][33] Although myocardial infarction is most frequently the consequence of local thrombosis, ischemic strokes more frequently result from embolic disorders. 34 TM expression has been demonstrated in brain vessels, because TM mRNA expression is present in the blood-brain barrier 35 and protein C is activated in jugular vein blood during carotid artery occlusion in humans. 36 The endothelial TM expression in brain is constitutively downregulated by astrocytes and acutely downregulated by pathogenic mediators of ischemic stroke, such as interleukin-1␤ and tumor necrosis factor-␣.…”
Section: Erk2mentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Although myocardial infarction is most frequently the consequence of local thrombosis, ischemic strokes more frequently result from embolic disorders. 34 TM expression has been demonstrated in brain vessels, because TM mRNA expression is present in the blood-brain barrier 35 and protein C is activated in jugular vein blood during carotid artery occlusion in humans. 36 The endothelial TM expression in brain is constitutively downregulated by astrocytes and acutely downregulated by pathogenic mediators of ischemic stroke, such as interleukin-1␤ and tumor necrosis factor-␣.…”
Section: Erk2mentioning
confidence: 99%
“…36 The endothelial TM expression in brain is constitutively downregulated by astrocytes and acutely downregulated by pathogenic mediators of ischemic stroke, such as interleukin-1␤ and tumor necrosis factor-␣. 35 Interestingly, astrocyteinduced downregulation of TM endothelial expression occurs through transforming growth factor-␤ secretion, 37 known to enhance endothelial cell proliferation. 38 Overall, that TM …”
Section: Erk2mentioning
confidence: 99%
“…Although TM is abundant in most systemic vasculature, immunohistochemical studies 4 -7 have revealed only limited, if any, TM expression in the human cerebrovasculature. A restricted functional role for PC activation in the central nervous system is further suggested by findings 8 that astrocyte coculture produces a 20-fold downregulation of endothelial cell TM mRNA production in vitro. Hence, the importance of the PC antithrombotic mechanism in brain has not yet been established, and it is unknown whether functional TM is present in sufficient quantity to generate APC during cerebrovascular insufficiency.…”
mentioning
confidence: 98%
“…We have demonstrated that astrocytes regulate endothelial expression of both tPA and TM in vitro. 36,37 The mechanism of this action has been uncertain. Astrocytes can secrete a number of cytokines and growth factors known to modulate endothelial function, including transforming growth factor-␤ (TGF-␤).…”
mentioning
confidence: 99%